The concept of triple Helix extended model in Lodz in the light of own work = Koncepcja rozszerzonego modelu potrójnej Heliksy w Łodzi w świetle badań własnych - Trippner-Hrabi, Justyna (Zielona Góra: Faculty of Economics and Management Press)
The functioning and development of enterprises are determined by transferring up-to-date knowledge into their structures. Therefore, entities being market leaders should enter into cooperation with scientific units which are providers of new solutions as well technical as organizational ones. Such cooperation in the region should be carried out with the participation of local authorities whose job is multi-dimensional and long-term support for the parties involved.
Keywords: zarządzanie wiedzą; zespoły wiedzy; kooperacja; przedsiębiorstwo; knowledge management; knowledge teams; cooperation; enterprises